Organoleptic Value and Number of Bacteria Sausage Rabbit Meat Based On Levels Green Bean Flour Substitution - D.W. Sari; Bulkaini Bulkaini; Djoko Kisworo (Jurnal Biologi Tropis, 2021)
Sausage is a food ingredient that comes from pieces of meat that are ground and seasoned, and put into a casing so that it is oval in shape.ÃÂ  One type of meat that can be processed into sausage is rabbit meat. This study aims to determine the effect of the level of substitution of mung bean flour on the organoleptic value and the number of bacteria in rabbit meat sausage. The research materials used were 3000 g rabbit meat, mung bean flour, skim milk, and a severala of spices. The experimental design used was a completely randomized design (CRD) with 4 treatments, namely the addition of 0%, 15%, 30% and 45% mung bean flour, with 4 replications. The results showed that the level of substitution of mung bean flour had a significant effect (P<0.05) on the color, taste and texture of rabbit meat sausage and had no significant effect (P>0.05) on the aroma and number of bacteria. The addition of 15% mung bean flour gave the best organoleptic values, namely: Color 5.28 (light), aroma 5.31 (good), taste 5.95 (tasty), texture 5.99 (soft) with a bacterial count of 2.00 x 103 cfu/g, which is below the standard for bacterial contamination of sausages set by SNI 1995, which is 1x 103 cfu/g.